PENGARUH KOMPETENSI PEDAGOGIK GURU TERHADAP MINAT BELAJAR SISWA SMA NEGERI 6 MANDAU KABUPATEN BENGKALIS - Yusni Lastiar Yusni Lastiar; Gimin '; Syakdanur Nas Syakdanur Nas (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: According to the UUD 1945 paragraph IV, one of Indonesia’s aim is make this nation getting smarter. In order to reveal that aim, we need to do an effort such as the developing human resource with the improvement of education qualities. This research held in SMA Negeri6 Mandau Kabupaten Bengkalis to analyze the influence of pedagogical competence due to the interest in learning for students in SMA Negeri6 Mandau Kabupaten Bengkalis. With the proporsion random sampling technique, the researcher got 52 students as the sample of this research. The analyses technique use descriptive quantitative analyses with using simple regression linier equation that proceeded with SPSS 16.00 version. Based on the research result, the influence of teacher’s pedagogical competence is significance enough due to the learning interest of the students in SMA Negeri6 Mandau Kabupaten Bengkalis. Based on the significance experiment result that held with result F count (9,065) ≥ F table (4,03) with Sig (0,0004) ≤ (0,05). It means that is rejectedand is accepted. the result of simple regression linier equation is Y = 31,810 + 0.503X. it is show us that without pedagogical competence, students learning interest is 31,810 and for every 1 improvement of teacher’s pedagogical competence will improve 0.503X students learning interest. On regression analyses calculation the researcher got 0,513 RSquare of contribution to students learning interest. It means that pedagogical competence variable gives contribution to students learning interest in SMA Negeri 6 Mandau 15,3% and rest 84,7 % influenced by other variables. Key words : Pedagogical Competence, Learning Interest